Sticky seeds: Why old seeds continue to dominate the rice-wheat agriculture in Eastern India - Kishore, Avinash; Singh, Vartika; Gupta, Shweta; International Maize and Wheat Improvement Center; International Rice Research Institute (Cereal Systems Initiative for South Asia, 2020)
Preliminary findings of a joint ICAR-IFPRI survey covering more than 2,000 farmers from 40 districts of Bihar, eastern Uttar Pradesh and Odisha show that the adoption of improved varieties of rice and wheat seeds is slow in the region. The average age of wheat varieties grown in Bihar and eastern Uttar Pradesh is 25-30 years. A 2016 study of varietal adoption of wheat by CIMMYT and the Michigan State University (MSU) in Bihar also reports similar findings (Ray and Maredia, 2016). The average age of non-hybrid rice varieties grown in the region is around the same. The situation is even worse for pulses where landraces of unknown origins dominate the cropped area. More than 90% of pulse growers in our sample in Bihar and Odisha could not recall the names of the seed varieties they had sown. The two state governments are implementing programs with subsidies, extension and participatory seed production programs to popularize rice and wheat varieties that are less than 10 years old and pulse varieties that are less than 15 years old. The IFPRI-ICAR survey shows that these programs have had limited impact. Rice and wheat together cover more than two-thirds of the gross cropped area (GCA) in Bihar and eastern Uttar Pradesh and rice alone accounts for 46% of GCA in Odisha. Why is the adoption of improved seeds so slow for the main crops in these states?